Introduction to animal rights : your child or the dog? - Francione, Gary L. (Gary Lawrence), 1954- (Temple University Press, 2000)
Argues that the way humans treat animals results from the contradiction between the ideas that animals have some rights, but that they are also property, and offers ways to resolve the conflict.